2017
DOI: 10.1097/opx.0000000000001044
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation and Phoria in Children Wearing Multifocal Contact Lenses

Abstract: Purpose To determine the effect of multifocal contact lenses on accommodation and phoria in children. Methods This was a prospective, non-dispensing, randomized, crossover, single visit study. Myopic children with normal accommodation and binocularity and no history of myopia control treatment were enrolled and fitted with Coopervision Biofinity single vision (SV) and multifocal (MF, +2.50D center distance add) contact lenses. Accommodative responses (photorefraction) and phorias (Modified Thorington) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 39 publications
8
67
1
1
Order By: Relevance
“…This suggests that the concentric, alternating power profile of the Clinical and Experimental Optometry 103.1 January 2020 lenses causes changes in HOAs that are markedly pupil-dependent. Multifocal contact lenses have been shown to affect the accommodation response; 187,188 however, the change in HOAs during accommodation with multifocal contact lens wear is yet to be examined. Future studies examining the change in HOAs during accommodation while wearing dual-focus and multifocal contact lenses may provide valuable insights into accommodative function during lens wear and potential mechanisms for myopia control.…”
Section: Soft Contact Lenses: Multifocal and Dual-focusmentioning
confidence: 99%
“…This suggests that the concentric, alternating power profile of the Clinical and Experimental Optometry 103.1 January 2020 lenses causes changes in HOAs that are markedly pupil-dependent. Multifocal contact lenses have been shown to affect the accommodation response; 187,188 however, the change in HOAs during accommodation with multifocal contact lens wear is yet to be examined. Future studies examining the change in HOAs during accommodation while wearing dual-focus and multifocal contact lenses may provide valuable insights into accommodative function during lens wear and potential mechanisms for myopia control.…”
Section: Soft Contact Lenses: Multifocal and Dual-focusmentioning
confidence: 99%
“…Studies of accommodation in young adults (non‐presbyopic) wearing multifocal lenses reveal either normal or reduced gain behaviour beyond the far point of the near add . Similarly, diverse accommodative gains have been observed in children (aged 7–16 years) viewing with multifocal lenses with some exhibiting normal, and some reduced, gain …”
Section: Introductionmentioning
confidence: 99%
“…Visual performance with bi-and multifocal soft contact lenses was previously investigated in pre-presbyopic subjects with respect to the quality of vision [12][13][14] and changes in the accommodation behaviour 7,[15][16][17][18][19][20][21][22] . A recent investigation by Gong et al 23 showed that children fitted with centre-distance multifocal soft contact lenses with a positive addition of +2.5 D (Biofinity, comfilcon A, Cooper Vision) used the lenses' addition power during near vision to relax their accommodation. This underaccommodation at near could increase the peripheral hyperopic defocus and thus possibly counteract the contact lenses' therapeutic effect during near vision tasks 23 .…”
mentioning
confidence: 99%